A GOIABEIRA E OS ARAÇÃZEIROS DESCRITOS POR PISO E MARCGRAV NO SÉCULO 17, DO NORDESTE - Pickel, D. Bento (REVISTA DE AGRICULTURA, 2016)
A GOIABEIRA E OS ARAÇÃZEIROS DESCRITOS POR PISO E MARCGRAV NO SÉCULO 17, DO NORDESTE